Numerical Modeling of the Blend Morphology Evolution in Twin‐Screw Extruders. Issue 3 (11th February 2022) - Wong, Wing‐Hin B.; de Bie, Vincent G.; Hulsen, Martien A.; Anderson, Patrick D.
Abstract: The blend morphology model developed by Wong et al., based on Peters et al., is used to investigate the development of the disperse polymer blend morphology in twin‐screw extruder flow. First, the model is written in a point‐wise form suitable for using in conjunction with particle tracking. Particle tracking methods are used to generate trajectories along the flow field. Macroscopic droplet populations are placed along these trajectories and the velocity gradient tensor is extracted and applied on the point‐wise blend morphology model. Very large morphology differences arise between trajectories that pass through the middle gap and those that do not. In the global distribution of (macroscopically averaged, monodisperse) droplet sizes, two distinct peaks appear due to these different trajectories. Given enough number of screw rotations, a droplet population can reach almost every position in the twin‐screw extruder and travel along both types of particle trajectories. The effect of varying the gap size is that the largest droplets are unaffected, but the smallest droplets are smaller for a smaller gap size due to the higher maximum shear rate. The effect of varying the viscosity ratio on the global droplet size distribution is found to be nonlinear and is strongly determined by the Grace curve. The effect on polydisperse droplet populations is found to be that trajectories that do not pass through the gap evolve toward a single peak, whereas trajectories that do pass through the gap lead to a split into two peaks that ultimately rejoin as one peak. It is concluded that the initial position of a population in the twin‐screw extruder has a very large effect on the developing transient blend morphology, though future work should be done on the importance of the initial position on the steady‐state blend morphology after a very large number of screw rotations. Abstract : The properties of disperse polymer blends depend strongly on their morphology. This work presents a phenomenological model and numerical results of the evolution of this morphology in a twin‐screw extruder flow field for given initial conditions. In particular, the effects of the gap size between the screws and viscosity ratio on the morphology evolution are studied.